Translating Male and Female Discourses in 'Between the Acts' - Škopljanac, Lovro (Array, 2012)
The paper deals with conceptual and practical work involved in translating V. Woolf's novel "Between the Acts" into Croatian. It also examines "the problematic issues of translating gender, where the passage from English, a neutral language, to a gendered one (Spanish, German, Croatian and Italian) nourishes a vivacious debate on translation choices". (O. Palusci).